Development of nanoemulsions containing Physalis peruviana calyx extract: A study on stability and antioxidant capacity. (November 2019) - Bazana, Maiara Taís; da Silva, Suelen Santos; Codevilla, Cristiane Franco; de Deus, Cassandra; Lucas, Bruna Nichelle; Ugalde, Gustavo Andrade; Mazutti, Marcio Antonio; Moraes Flores, Erico Marlon; Barin, Juliano Smanioto; de Bona da Silva, Cristiane; de Menezes, Cristiano Ragagnin
Abstract: The aim of this study was to develop and evaluate the physicochemical and antioxidant stability of nanoemulsions containing a Physalis peruviana calyx extract (CPp-NE) and free extracts under different storage conditions (7 and 25 °C) and with absence or incidence of light for 120 days. The calyx extracts were prepared with ethanol 60% and characterized for later preparation of the nanoemulsions by spontaneous emulsification. The formulations presented nanometric sizes, low polydispersity index, negative zeta potential, acid pH, rutin content (11 μg·mL −1 ), and encapsulation efficiency of 85%. Regarding the stability, the droplet size and PdI of the CPp-NE stored at refrigeration temperature in the dark, room temperature in the dark, and refrigeration temperature with light incidence were stable for 120 days and with no visible changes in the formulations. The antioxidant capacity was related to the reducing capacity, and the best results were found for nanoemulsions stored at room temperature and in absence of light. In addition, CPp-NE presented higher antioxidant and reducing capacity in relation to the free extracts. Graphical abstract: Unlabelled Image Highlights: Nanoemulsions containing the Physalis peruviana calyx extract were developed. The formulations showed nanometric sizes, low PdI, negative zeta potential, and acid pH. The major compound found was rutin and 85% encapsulation efficiency. Nanoemulsions stored at room temperature in the dark presented the best results. Nanoemulsions were able to protect the bioactive compounds more than the free extract.